Pengaruh Ukuran Dewan Komisaris dan Keahlian Komite Audit terhadap Kualitas Pelaporan Keuangan di Sektor Kesehatan - Nurcahyati, Sintiya; Anshari, Rahman; Pribadi, Muhammad Iqbal (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of board size and audit committee expertise on the quality of financial reporting in healthcare sector companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2023. The healthcare sector was selected due to its complex financial systems and high risk of financial statement manipulation, requiring strong and transparent governance. A quantitative approach with purposive sampling was employed, resulting in 106 observations. Multiple linear regression analysis was used to assess the effect of each independent variable on financial reporting quality. The findings indicate that neither board size nor audit committee expertise has a significant effect on financial reporting quality. This suggests that formal governance structures alone do not guarantee high-quality reporting without effective oversight. For example, PT Kimia Farma Tbk achieved a Good Corporate Governance score of 96.48 in its 2022 Annual Report but still posted a net loss of IDR 170.04 billion, showing that formal expertise in audit committees does not automatically prevent reporting quality issues. The results highlight that effective oversight is driven more by independence, active participation, and a strong governance culture than by technical background or the number of supervisory members. This study contributes to understanding the limitations of formal governance mechanisms in strategic sectors.